Right Ventricular Failure Post LVAD Implantation Corrected with Biventricular Support: An In Vitro Model. Issue 1 (January 2017) - Shehab, Sajad; Allida, Sabine M.; Davidson, Patricia M.; Newton, Phillip J.; Robson, Desiree; Jansz, Paul C.; Hayward, Christopher S.
Abstract : Right ventricular failure after left ventricular assist device (LVAD) implantation is associated with high mortality. Management remains limited to pharmacologic therapy and temporary mechanical support. Delayed right ventricular assist device (RVAD) support after LVAD implantation is associated with poorer outcomes. With the advent of miniaturized, durable, continuous flow ventricular assist device systems, chronic RVAD and biventricular assist device (BiVAD) support has been used with some success. The purpose of this study was to assess combined BiVAD and LVAD with delayed RVAD support within a four-elemental mock circulatory loop (MCL) simulating the human cardiovascular system. Our hypothesis was that delayed continuous flow RVAD (RVAD) would produce similar hemodynamic and flow parameters to those of initial BiVAD support. Using the MCL, baseline biventricular heart failure with elevated right and left filling pressures with low cardiac output was simulated. The addition of LVAD within a biventricular configuration improved cardiac output somewhat, but was associated with persistent right heart failure with elevated right-sided filling pressures. The addition of an RVAD significantly improved LVAD outputs and returned filling pressures to normal throughout the circulation. In conclusion, RVAD support successfully restored hemodynamics and flow parameters of biventricular failure supported with isolated LVAD with persistent elevated right atrial pressure.